A Communication Model for Non-fiction Interactive Digital Narratives: A Study of Cultural Heritage Websites - BASARABA, NICOLE (My University, 2018)
Interactive digital narrative (IDN) is an umbrella term used to encompass the various formats of digital narrative such as hypertext fiction, transmedia stories, and video games. The study of IDNs transverses the disciplines of narratology, game studies, and media studies. The main question this article addresses is how does the digital medium affect narrative in cultural heritage websites? This question is examined by proposing a new communication model that considers the role of digital media — the Creator-Produser Transaction Model — and adapting existing “tools” of narrative analysis into a “narratological toolkit” for the study of non-fiction IDNs. The transaction between creators and produsers and how an IDN narratological toolkit can be applied are exemplified through the analysis of three cultural heritage websites: Open Monuments (“Otwarte Zabytki”), Belgian Refugees of 1914–1919, and Storymap.
PUBLISHED
Keywords: Creative Arts Practice; Creative Technologies; Digital Engagement; Digital Humanities; Language and/or Literature, Non-Fiction; digital narrative